Implementing Deep Learning in the EFL Classroom: Strategies for Fostering Mindful, Meaningful, and Joyful Language Learning - Benu, Naniana N.; Beeh, Norci; Nenotek, Seprianus A. (Journal of Language, Education, Literature, and Culture, 2025)
This article explores the application of the deep learning approach in learning English as a Foreign Language (EFL) at the secondary school level, focusing on integrating mindful learning, meaningful learning, and joyful learning. This study uses a descriptive-analytical theoretical study method by reviewing literature from various scientific sources. The analysis results reveal that the basic principles of deep learning include deep cognitive engagement, contextual connections, and metacognitive reflection, which complement each other to create a deep and meaningful learning experience. In addition, the three learning concepts, mindful, meaningful, and joyful learning, contribute to a holistic approach to language learning, enhancing students' linguistic abilities and building emotional resilience and cultural awareness. The proposed adaptation strategies include the implementation of project-based assignments, gradual scaffolding with affective support, cross-curricular theme integration, and the use of responsive technologies. However, challenges such as exam-oriented curriculum, student resistance to reflective methods, and limitations in teacher training need to be addressed to support the effective implementation of this approach. The theoretical implications of this study pave the way for the recontextualization of constructivist theory and the development of holistic assessment models in language education. This article provides new insights into how innovative approaches can improve the quality of EFL learning and its relevance in facing the challenges of an increasingly complex global world.